The role of Toxoplasma gondii as a possible inflammatory agent in the pathogenesis of type 2 diabetes mellitus in humans. Issue 4 (1st December 2016) - Molan, Aus; Nosaka, Kazunori; Hunter, Michael; Wang, Wei
Abstract : Type 2 diabetes mellitus (T2DM) continues to be a major challenge for public health authorities worldwide. While potential causes such as obesity, physical inactivity, and dietary patterns have been proposed to explain the growing epidemic, there may also be unidentified environmental determinants. An emerging field of research is starting to examine the association of infectious and environmental pathogens with diabetes. In particular, the potential of these pathogens to cause low-grade inflammation that facilitates the risk and development of T2DM. An understudied pathogen of potential interest is the protozoan parasite Toxoplasma gondii (T. gondii). There is limited clinical evidence supporting the association between chronic T. gondii infection and the development of many disorders, including T2DM, in both animals and humans. This review (1) addresses the existing knowledge of the role of T. gondii in the inflammation process leading to T2DM, (2) examines the current studies describing the relationship between T. gondii and T2DM, and (3) makes recommendations for future studies to determine the role of T. gondii in the pathogenesis of T2DM. We believe that T. gondii may be an important target for T2DM intervention, and propose a new field of study, "toxoplasmic type 2 diabetes."